Experimental evaluation of the MPPT hardware for vehicle solar arrays with silicon junction cells - Li, Q.; Wolfs, Peter (Curtin University, 2007)
This paper studies the design of the solar vehicle distributed maximum power point tracking (MPPT) hardware intended for silicon junction cell applications. The MPPT hardware operates in an input voltage range from 0.9 V to 1.8 V and is suited for a power tracking group of four series connected silicon cells. The finished MPPT hardware measures 17 mm by 21 mm and has a nominal power rating of 600 mW. The power loss measurement through the calorimetric method verifies a power conversion efficiency of 93.9%. An analogue solar cell simulator is also employed to evaluate the performance of the MPPT hardware. The experimental results are shown at the end of the paper and confirm that high tracking accuracy has been achieved under both the static and the dynamic insolation conditions.